2010
DOI: 10.3390/molecules15085124
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Aggregation and Platelet Activating Factor (PAF) Receptor Antagonistic Activities of the Essential Oils of Five Goniothalamus Species

Abstract: Nine essential oils, hydrodistilled from different parts of five Goniothalamus species (G. velutinus Airy-Shaw, G. woodii Merr., G. clemensii Ban, G. tapis Miq. and G. tapisoides Mat Salleh) were evaluated for their ability to inhibit platelet aggregation in human whole blood using an electrical impedance method and their inhibitory effects on platelet activating factor (PAF) receptor binding with rabbit platelets using 3H-PAF as a ligand. The chemical composition of the oils was analyzed by gas chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…There was also inhibition (50 %) of AA-induced platelet aggregation (with an IC 50 of 93.6 μg/ml). Aspirin, which was used as the positive control in the study, was found to be a more potent cyclooxygenase inhibitor, since its IC 50 was much lower (4.5 μg/ml or 24.8 μM) than those of the oils investigated [42]. Furthermore, it is suggested that the antiplatelet activity of the Goniothalamus oils may not be due solely to any individual component but could be due to the synergistic effect of a combination of its compounds.…”
Section: +mentioning
confidence: 96%
See 4 more Smart Citations
“…There was also inhibition (50 %) of AA-induced platelet aggregation (with an IC 50 of 93.6 μg/ml). Aspirin, which was used as the positive control in the study, was found to be a more potent cyclooxygenase inhibitor, since its IC 50 was much lower (4.5 μg/ml or 24.8 μM) than those of the oils investigated [42]. Furthermore, it is suggested that the antiplatelet activity of the Goniothalamus oils may not be due solely to any individual component but could be due to the synergistic effect of a combination of its compounds.…”
Section: +mentioning
confidence: 96%
“…Different parts of these plants are used in traditional medicine to treat conditions such as asthma, rheumatism, fever, malaria, cholera and stomach aches. The in vitro inhibitory effect of various oils from Goniothalamus species was observed for the first time, by Moharam et al [42]. The bark oil, identified as Gonystylus velutinus (100 μg/ml, distilled from Goniothalamus ) showed strong inhibition (51 %) of human platelet aggregation in whole blood, induced by ADP (10 μM, with an IC 50 of 87.7 μg/ml).…”
Section: +mentioning
confidence: 96%
See 3 more Smart Citations